ANALYSIS OF PERSONNEL RADIATION DOSES DURING X-RAY PROCEDURES - Lee M. V. (Bright Mind Publishing, 2025)
The article is devoted to the study of the problem of occupational exposure of personnel in healthcare organizations and a comparative assessment of radiation levels. An analysis of 817 individual dose measurement results for personnel in Tashkent healthcare institutions over a 3-year period (2023–2025) was conducted. A comparison of average individual annual effective doses was performed for 4 groups of healthcare workers: X-ray technicians , radiologist, dental radiologists, and members of X-ray surgical teams (surgeons, anesthesiologists, and operating room nurses) working in close proximity to the radiation source. It is shown that the average annual effective dose for the first three groups of healthcare workers is 1.72 mSv . For members of X-ray surgical teams, the analogous value is 3.48 mSv . For the period 2023–2025. The individual annual effective radiation doses of personnel did not exceed the basic dose limits established by SanPiN 0193-06 "Radiation Safety Standards (NRB-2006) and Basic Sanitary Rules for Ensuring Radiation Safety (OSPORB-2006)." The accuracy of effective dose assessment based on individual dose equivalent measurements was also examined.
Keywords: Personnel, medical organization, individual dosimetric monitoring, thermoluminescent method, individual dose equivalent, effective dose